49.4k views
5 votes
Simplify-3square root2+3square root 8

User Stockton
by
5.1k points

2 Answers

3 votes

Explanation:

3

2

2

2

Pull terms out from under the radical.

3

(

2

2

)

Multiply

2

by

3

.

6

2

The result can be shown in multiple forms.

Exact Form:

6

2

Decimal Form:

8.48528137

User Vignesh I
by
5.1k points
5 votes

For this case we must simplify the following expression:


3 \sqrt {2} +3 \sqrt {8}

We rewrite:


8 = 2 ^ 3 = 2 ^ 2 * 2\\3 \sqrt {2} +3 \sqrt {2 ^ 2 * 2} =

For properties of potecnias and roots we have that:


\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}

Then, rewriting the expression:


3 \sqrt {2} + 2 * 3 \sqrt {2} =\\3 \sqrt {2} +6 \sqrt {2} =\\9 \sqrt {2}

Answer:


9 \sqrt {2}

User Charlie Haley
by
5.5k points